2009
DOI: 10.1093/intimm/dxn137
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of type I hypersensitivity in experimental allergic conjunctivitis by eotaxin-1/CCR3 blockade

Abstract: The immune response is regulated, in part, by effector cells whose activation requires multiple signals. For example, T cells require signals emanating from the T cell antigen receptor and co-stimulatory molecules for full activation. Here, we present evidence indicating that IgE-mediated hypersensitivity reactions in vivo also require cognate signals to activate mast cells. Immediate hypersensitivity reactions in the conjunctiva are ablated in mice deficient in eotaxin-1, despite normal numbers of tissue mast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
24
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 35 publications
4
24
0
Order By: Relevance
“…We recently showed that ablation of eotaxin-1 significantly suppresses allergen-induced signs in the eyes and mast cell degranulation. 8 Thus, both CCR1-and CCR3-mediated signals appear to be necessary for optimal mast cell activation. This implicates that the CC chemokine-receptors may serve as indispensable stimuli for inflamed conjunctiva, although their relative importance needs to be carefully evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently showed that ablation of eotaxin-1 significantly suppresses allergen-induced signs in the eyes and mast cell degranulation. 8 Thus, both CCR1-and CCR3-mediated signals appear to be necessary for optimal mast cell activation. This implicates that the CC chemokine-receptors may serve as indispensable stimuli for inflamed conjunctiva, although their relative importance needs to be carefully evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…For example, eotaxin-1, a CC chemokine, is a signature eosinophil mediator 6 but also serves as an allergenprimed mast cell activator. 7,8 MIP-1␣, another CC chemokine, is also necessary for mast cell activation. 9 Thus, the CC chemokines are critically involved in mast cell-mediated acute inflammation, and the allergen-primed mast cell degranulation leads to latephase eosinophilic inflammation.…”
mentioning
confidence: 99%
“…These data highlight some of the difficulties in the mast cell field, with contrasting observations from in vitro and in vivo experimental systems. For CCL11, these differences may be reconciled with data suggesting that the CCL11ÀCCR3 axis may be more involved with mast cell development, rather than migration [60]. This is highlighted by the finding that immediate hypersensitivity reactions in the conjunctiva are ablated in mice deficient in CCL11, despite normal numbers of tissue mast cells and concentration of IgE.…”
Section: Direct and Indirect Recruitment Of Mast Cells By Chemokinesmentioning
confidence: 96%
“…We reported that mice deficient for CCL11 or treated with a neutralizing Ab to this chemokine displayed reduced mast cell degranulation and impaired immediate hypersensitivity responses (12). Furthermore, mice deficient for CCR3 showed reductions in early-phase allergic symptoms, vascular leakage, and conjunctival eosinophil recruitment in a mouse model of allergic conjunctivitis (13)(14)(15).…”
mentioning
confidence: 97%